Javatpoint Logo
Javatpoint Logo

Recurrence Relation

A recurrence is an equation or inequality that describes a function in terms of its values on smaller inputs. To solve a Recurrence Relation means to obtain a function defined on the natural numbers that satisfy the recurrence.

For Example, the Worst Case Running Time T(n) of the MERGE SORT Procedures is described by the recurrence.

T (n) = θ (1) if n=1
 2TDAA Recurrence Relation + θ (n) if n>1

There are four methods for solving Recurrence:

  1. Substitution Method
  2. Iteration Method
  3. Recursion Tree Method
  4. Master Method

1. Substitution Method:

The Substitution Method Consists of two main steps:

  1. Guess the Solution.
  2. Use the mathematical induction to find the boundary condition and shows that the guess is correct.

For Example1 Solve the equation by Substitution Method.

	T (n) = TDAA Recurrence Relation + n

We have to show that it is asymptotically bound by O (log n).


For T (n) = O (log n)

We have to show that for some constant c

Put this in given Recurrence Equation.

	T (n) ≤c logDAA Recurrence Relation+ 1
			≤c logDAA Recurrence Relation+ 1 = c logn-clog2 2+1
			≤c logn for c≥1
Thus T (n) =O logn.

Example2 Consider the Recurrence

T (n) = 2TDAA Recurrence Relation+ n n>1

Find an Asymptotic bound on T.


We guess the solution is O (n (logn)).Thus for constant 'c'.
 T (n) ≤c n logn
Put this in given Recurrence Equation.
  T (n) ≤2cDAA Recurrence Relationlog DAA Recurrence Relation+n
      =cn logn-n (clog2-1)
      ≤cn logn for (c≥1)
Thus T (n) = O (n logn).

2. Iteration Methods

It means to expand the recurrence and express it as a summation of terms of n and initial condition.

Example1: Consider the Recurrence


T (n) = 2T (n-1)
      = 2[2T (n-2)] = 22T (n-2)
      = 4[2T (n-3)] = 23T (n-3)
      = 8[2T (n-4)] = 24T (n-4)   (Eq.1)

Repeat the procedure for i times

T (n) = 2i T (n-i)
Put n-i=1 or i= n-1 in    (Eq.1)
T (n) = 2n-1 T (1)
      = 2n-1 .1    {T (1) =1 .....given}
      = 2n-1 

Example2: Consider the Recurrence


 T (n) = T (n-1) +1
       = (T (n-2) +1) +1 = (T (n-3) +1) +1+1
       = T (n-4) +4 = T (n-5) +1+4
       = T (n-5) +5= T (n-k) + k
Where k = n-1
   T (n-k) = T (1) = θ (1)
   T (n) = θ (1) + (n-1) = 1+n-1=n= θ (n).

Youtube For Videos Join Our Youtube Channel: Join Now


Help Others, Please Share

facebook twitter pinterest

Learn Latest Tutorials


Trending Technologies

B.Tech / MCA